2011
DOI: 10.1159/000323390
|View full text |Cite
|
Sign up to set email alerts
|

Nationwide Population-Based Epidemiologic Study of Cryptococcal Meningitis in Taiwan

Abstract: Background: Little is known about the epidemiology of cryptococcal meningitis in Taiwan. The aim of this study was to conduct the first nationwide population-based epidemiologic study of cryptococcal meningitis in Taiwan. Methods: Cases of cryptococcal meningitis were identified from the annual hospitalization discharge claims of the National Health Insurance Research Database with the corresponding ICD-9 code 321.0 from January 2000 to December 2007. Results: A total of 845 incident cases of cryptococcal meni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 36 publications
3
12
0
Order By: Relevance
“…Similar to the incidence in children of Taiwan with unknown HIV status reported previously [11], we found an average annual incidence of 4.3 cases of CM per million HIV-negative children with a fatality rate of 1.7% in mainland China.…”
Section: Discussionsupporting
confidence: 88%
“…Similar to the incidence in children of Taiwan with unknown HIV status reported previously [11], we found an average annual incidence of 4.3 cases of CM per million HIV-negative children with a fatality rate of 1.7% in mainland China.…”
Section: Discussionsupporting
confidence: 88%
“…A recent systemic review by Yuchong et al (21) summarized 1,032 reports of 8,769 cases of pulmonary cryptococcosis in mainland China between 1985 and 2010. Notably, these rates were similar to those reported in Taiwan, where the average annual incidence increased from 4.0 cases per million individuals in 2000 to 5.5 per million individuals in 2007 (22). Considering the aforementioned studies, it is evident that pulmonary cryptococcosis cases in China have been increasing over the recent decades (19,21,23).…”
Section: Discussionsupporting
confidence: 80%
“…However, different from tubercular meningitis, obliteration of basilar cistern and meningeal enhancement were less common in cryptococcal meningitis. Furthermore, cranial nerve impairment and intracranial venous sinus thrombosis were detected in our study, which was rarely reported before [6]. …”
Section: Discussionsupporting
confidence: 56%
“…This is followed by primary immunodeficiencies, diabetes, and requiring glucocorticosteroid therapy or organ transplantation. On the contrary, studies [5, 6] in China demonstrated that 50–77% of patients with cryptococcal meningitis exhibited normal immune function. However, disseminated cryptococcosis is rare in immunocompetent children, and is mostly localized in the brain or lungs [7].…”
Section: Introductionmentioning
confidence: 99%